BS EN 4165-008. Aerospace series. Connectors, electrical, rectangular, modular. Operating temperature 175 °C continuous. Part 008. Rack and panel plug for 2 and 4 modules, series 2. Product standard (5th August 2021) - British Standards Institution,
No abstract available